Odpowiedzi

2010-03-01T18:55:05+01:00
A) 6x² - x - 2 =0
Δ=(-1)²-4*6*(-2)=1+48=49
√Δ=7
x₁=(1-7):2*6=-6:12=-½
x₂=(1+7):2*6=8:12=⅔
b) 2x² + x - 1 <0
Δ=1²-4*2*(-1)=1+8=9
√Δ=3
x₁=(-1-3):2*2=-4:4=-1
x₂=(-1+3):2*2=2:4=½
x∈(-1;½)
2010-03-01T19:05:34+01:00
A)
6x(kw) - x - 2 = 0
delta = b(kw) - 4ac = 1 - 4*6*(-2) = 49
pierwiastek z delty = 7
X1= -b- pierw. z delty / 2a
X1= 1-7/12 = -6/12 = -1/2
X2= -b+ pierw. z delty / 2a
X2= 1+7/12 = 8/12 = 2/3

b)
2x(kw) + x -1 < 0
delta = 1 - 4*2*(-1) = 9
pierw. z delty = 3
X1= -1 - 3 / 4 = -4/4 = -1
X2= -1+3/4 = 2/4=1/2